2019
DOI: 10.1161/hypertensionaha.118.12380
|View full text |Cite
|
Sign up to set email alerts
|

VEGF (Vascular Endothelial Growth Factor) Functionalized Magnetic Beads in a Microfluidic Device to Improve the Angiogenic Balance in Preeclampsia

Abstract: Preeclampsia is a hypertensive pregnancy disease associated with a massive increase in sFlt-1 (soluble form of the vascular endothelial growth factor 1) in the maternal circulation, responsible for angiogenic imbalance and endothelial dysfunction. Pilot studies suggest that extracorporeal apheresis may reduce circulating sFlt-1 and prolong pregnancy. Nonspecific apheresis systems have potential adverse effects because of the capture of many other molecules. Our concept is based on a specific and competitive ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The increase in HIF in a hypoxic condition is associated with VEGF activity [23, 24]. The increase in the activity and expression of VEGF in situations of high blood pressure, such as preeclampsia, is well known [25]. Zhang et al [26] showed how increased VEGF activity in placentas in preeclampsia produced an increase in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in HIF in a hypoxic condition is associated with VEGF activity [23, 24]. The increase in the activity and expression of VEGF in situations of high blood pressure, such as preeclampsia, is well known [25]. Zhang et al [26] showed how increased VEGF activity in placentas in preeclampsia produced an increase in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF), a biomarker of angiogenesis, is necessary for promoting placental vascularization. It has been suggested that a decrease in VEGF in pregnant women may affect the recasting of the uterine spiral artery, potentially leading to PE 10 …”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a decrease in VEGF in pregnant women may affect the recasting of the uterine spiral artery, potentially leading to PE. 10 wGhrelin, a 28 amino-acid hormone produced primarily by the stomach, was initially shown to strongly stimulate growth hormone release, promote food intake and regulate energy homeostasis by binding to its specific receptor, GHSR1a. Ghrelin has been shown to stimulate endothelial cells angiogenesis through extracellular regulated protein kinases (ERK) signaling pathway 11 and has been found to be in the regulation of blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…9 Indeed, competitive binding of sFlt-1 with VEGF has been shown to abolish the biological functions of VEGF and PLGF, leading to endothelial dysfunction. 10 In patients with preeclampsia, the ratio of sFlt1 to PLGF may be useful as a biomarker to predict preeclampsia. For instance, urinary sFlt-1/PLGF ratio is reported to be effective in differentiating women with severe preeclampsia from healthy pregnant women, 11 and patients with preeclampsia have been shown to have increased serum levels of sFlt-1, and decreased circulating PLGF.…”
Section: Introductionmentioning
confidence: 99%